Giving to versus taking from in- and out-group members - Marius Alt; Carlo Gallier; Achim Schlüter; Katherine M. Nelson; Eva Anggraini (Games, 2018)
In this experiment, we test whether subjects' responses to variations in the action set in a dictator game depends on induced group identities. The action set includes choices in which the dictator can either give money to or take money from the other player. As an extension to the anonymous setting, we introduce induced group identities using the minimal group paradigm. Based on a dictator game conducted with more than 300 students in Indonesia, we implement a full factorial design in order to analyze the framing of the action set in a varied cultural context and to examine varied prevalence of social norms given a group identity context. If group identity is not salient, we find that participants are slightly more generous when they have an opportunity to give to rather than to take from the recipient. However, when participants are matched with in-group members, this result is reversed and highly significant. The result of differing responses to framing effects in within-group interactions compared to a neutral setting are largely ascribed to the varied compliance with existing social norms.
Keywords: 330; social preferences; dictator game; giving and taking; social identity